2020
DOI: 10.23887/jere.v4i1.23959
|View full text |Cite
|
Sign up to set email alerts
|

Novice Versus Experienced Teachers: How They Transform Their Vulnerability Into Professional Identity in an Indonesian Junior High School

Abstract: The quality of education is influenced by many factors, one of which is the quality of the teachers. In the spirit of fostering a strong and resilient young generation, teachers in the capital city of Nusa Tenggara Timur (NTT), Kupang, attempted to break through their limitations in order to form their identity. This research investigated how novice and experienced teachers shifted their vulnerability into professional identity and to what extent this strategy impacted on their professional identity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…While the ultimate term talks more about the tangible results obtained by the teachers who have already possessed a higher level of resilience such as fully professional development, a stronger commitment to their works, great teaching passion, big pleasure, and laudable personalities. Florida and Mbato (2020) discovered that it is essential for both novice and experienced teachers to possess a higher degree of resilience while facing with many kinds of impediments in their teaching vocation in order to develop their professional identities to the utmost levels. Lomi and Mbato (2020) found that limited access of teaching facilities, teaching supports, and trainings will bring negative impacts on the teachers' resilient in promoting better learning processes for the students in a rural area.…”
Section: The Importance Of Resilience To Preserve Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…While the ultimate term talks more about the tangible results obtained by the teachers who have already possessed a higher level of resilience such as fully professional development, a stronger commitment to their works, great teaching passion, big pleasure, and laudable personalities. Florida and Mbato (2020) discovered that it is essential for both novice and experienced teachers to possess a higher degree of resilience while facing with many kinds of impediments in their teaching vocation in order to develop their professional identities to the utmost levels. Lomi and Mbato (2020) found that limited access of teaching facilities, teaching supports, and trainings will bring negative impacts on the teachers' resilient in promoting better learning processes for the students in a rural area.…”
Section: The Importance Of Resilience To Preserve Identitymentioning
confidence: 99%
“…They suggested that current educational programs for novice teachers should be continuously reformed in correspond with nowadays educational contexts in order to prepare them to be more professional educators in the future. Florida and Mbato (2020) also proposed the urgent need for the teachers to conduct more profound critical reflections after doing their teaching practices in order to help them to be more mindful and critical in determining further teaching actions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance inadequate teaching resources, facilities or government support. Those factors happen in rural areas of Indonesia (Nurwidodo, Husamah, Rahardjanto, Mas'odi, & Mufrihah, 2017;Lomi & Mbato, 2020;Florida & Mbato, 2020). Study conducted by Nurwidodo, et al (2017) reveals that teachers in rural area are resilience to cope with insufficient situation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some recent studies have reported related issues such as English teachers' vulnerability, critical incidents, attrition and the struggles faced by the novice teachers in Indonesian rural areas that may influence their perception in teaching (Florida & Mbato, 2020;Kharismawan & Mbato, 2020;Lomi & Mbato, 2020;Putri & Kuswandono, 2020). Many novice teachers particularly those working in the rural areas face imminent struggles to stay in the profession (Lomi & Mbato, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many novice teachers particularly those working in the rural areas face imminent struggles to stay in the profession (Lomi & Mbato, 2020). In addition, many novice and experienced teachers may face burn out as the result of hard task demands (see Florida & Mbato, 2020;Kharismawan & Mbato, 2020). One may assume that pre-service teachers' beliefs and expectations about the task returns as provided by the governmental policies could stimulate positive perceptions, and make them believe that teaching is their destined career.…”
Section: Introductionmentioning
confidence: 99%